(3EjbGX GdfGFejf hEagGe GdbGFejfs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3agPg QSGdI (B.. (3eG GOYjfGg hCXgQfGg MjK cGf ddfGS aJfI HSHH GdPghd hGdZadI hgh GdEbOGe hGdTQhY dYHGOI HOfjI eMVI djSJ HhSjdI eKd GdKdGI hGdUhe hbQGAI GdbQBf (B...s
(3BNQgG (B:s
... (3hbO HjfG Pdc aj QSGFdfG GdSja GdUGQe hEfbGP GdgGdcjf hEjbGX GdfGFejf hLdGA GdbdhH aYdjc HgG hWGdYgG MJi JYde MbjbI ebGdfG hfbhd GdMeO ddg (B.s
(3efShNI Yf fSNI HNW GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\61s
(3cTa GdXfhf (B1\214s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs